“Aplicación web y móvil para sistematizar el control y registro de citas médicas del consultorio odontológico Integral Souri Del Barrio La Estación” - Chiluisa Osorio, Stefany Alejandra (2020)
This technological proposal was carried out in the SOURI Dental Clinic located in la Estación neighborhood, in which, an inadequate administration on control and registration of medical appointments of patients was the problem identified, where the managing medical appointments processes were carried out manually in diaries, notebooks, telephone calls, this incurs an excessive time use and office materials, for this reason, developing a web and mobile application to systematize the control and registration of medical appointments using free software tools was this research’s objective. at this one, research methodologies were used like